A case of hereditary sensory and autonomic neuropathy type 4 presenting with chronic trophic ulcers - Tilak, Kedar M.; Shamkuwar, Pratibha B. (International Journal of Research in Medical Sciences, 2019)
Hereditary Sensory and Autonomic Neuropathy (HSAN) is a rare group of diseases involving varying degrees of peripheral nervous system. It is classified into five main types. HSAN type 4 is associated with insensitivity to pain and temperature and anihidrosis. The method of this study was to authors present a case report of a 3 year-old boy with Hereditary Sensory and Autonomic Neuropathy Type 4 presenting with chronic ulcers. Conclusions of this study was to HSAN type IV is a rare condition. There is no definitive treatment available presently for this condition.